Recent advancements and sustainable solutions in adsorption-based cooling systems integrated with renewable energy sources and industrial waste heat: A review - Sumit Kumar Singh; Dibakar Rakshit; K Ravi Kumar; Anurag Agarwal (Cleaner Engineering and Technology)
This work aims to compile the factors that impact the adsorption system's performance. The functional performance and operations of adsorption cooling systems are greatly influenced by the mass and heat diffusion across the adsorber bed, adsorbates-adsorbent pairs, cycle type, cyclic period, and the adsorber bed design. Generally, enhancing heat transport across the bed will decrease the thermal resistance, shortening the cycle time and eventually increasing the COP. To enhance the operational efficiency of the adsorption system, researchers have explored a few more adsorption cycles in addition to those that have already been studied. Some of the typical cycles like the multiple-adsorber bed cycle, surface cascading adsorption cycle, thermal wave cycle, mass-recovery cycle, and heat recovery cycle, are discussed in this work, unlike the previous work, making it helpful for design basis and enhancing the system's performance. A system having numerous beds offers a continual cooling effect and having minimal dead mass operates more efficiently. Combining all the contributing elements listed above provides superior outcomes and efficient performance for adsorption cooling systems. Generally, adsorption cooling technology has been oversimplified which means they don't fully explain the detailed physics of adsorption cooling technology, making it less percolated and technically less efficient. Current studies aim to understand these complex intricate physics better so that the adsorption system can be improved and correlated with various notes of adsorption technology to make it more widely accessible for commercial use.